The Test Re-Test Reliability of A Novel Single Leg Hop Test (T-Drill Hop Test) - Rodney Negrete; Samantha Simms; Jacob Gross; Lucas Nunes Rabello; Matt Hixon; Ibrahim M. Zeini; Walter L. Jenkins; George J. Davies (North American Sports Medicine Institute, 2021)
# Background Functional training and testing are an important part of a comprehensive rehabilitation program stressing the neuromuscular system in ways that simulate athletic performance to help determine criteria for return to sport. There are numerous single leg hop tests that have been used for these purposes, however, the validity and clinical relevance has been questioned. Many of the functional performance tests assess only the sagittal plane or forward direction and may only partially assess a person's athletic abilities. There is a need for reliable and valid functional tests to assess in a multi-directional manner. # Purpose/Hypothesis The purpose of this study is to determine the test re-test reliability of a novel multi-directional timed single leg hop test (T-Drill Hop Test) for use in rehabilitation and performance assessments. # Study Design Cross-sectional reliability study. # Methods Fifty healthy recreationally active college age subjects, (23 males and 27 females) between the ages of 18 and 35, (mean age 23.48 with SD 3.82) consented to perform the test. The subjects hopped along a 10ft. x 10ft. "T" shaped course. Subjects performed two timed maximum effort trials of the T-Drill Hop Test on each leg with an interval of 3-7 days between the two testing days. Intraclass Correlation Coefficients (ICC) were calculated to determine intersession reliability. # Results The inter-rater reliability (ICC's) for the entire group of 50 subjects ranged between .98 and 1.00 suggesting excellent reliability. The bilateral comparison, utilizing paired t-tests, of the T-Drill Hop Test demonstrated no significant differences between the time scores for the dominant and non-dominant legs for either males or females (p>.05). # Conclusion This study demonstrates the T-Drill Hop Test has excellent test re-test reliability. These results are important prior to validation and utilization as a clinical functional performance test. # Levels of Evidence Level 2